As principais implicações da Lei 11.638/07 sobre os tributos diretos (Imposto de Renda Pessoa Jurídica e Contribuição Social sobre o Lucro Líquido) - Nascimento, Rodrigo Bellomi do (2012)
This research aims to provide information about the major implications of the Law 11.638/07 on the calculation of direct taxes. The Law 11.638/07 instituted several changes to accounting standards that provided conditions for the convergence of international accounting standards and mainly segregation between corporate accounting and tax accounting. The research will discuss about the Transitional Tax Regime (RTT), Control Accounting Tax Transition (FCONT), implemented by the Federal Revenue of Brazil (RFB), taxes on sales, tax reflections on the PIS / PASEP and COFINS and adjustments in the Book of Calculation of Taxable Income (LALUR), in order to neutralize the tax effects arising from the application of Law n. 11.638/2007. To achieve the goal, we carried out a qualitative study based on literature review of existing legislation, standards of technical pronouncements, and a few books ever published on the subject, seeking to characterize the likely effects arising from the Law on direct taxes. Ultimately, it is hoped that the reader visualize, through the arguments, the main implications of the Law 11.638/07 caused in direct taxes